Legal Reasoning: Epistemological Construction and Dialectics of Justice in Modern Law Enforcement - Zalva Zahiah Putri Hecinda; Achmad Miftah Farid (Universitas Muhammadiyah Surakarta, 2025)
This research aims to analyze the epistemological construction of legal reasoning as a bridge between abstract legal norms and concrete facts, as well as examine the dialectic between legal certainty, substantive justice and social benefit in modern law enforcement practices inera of digital disruption. The methodology used is normative-qualitative legal research based on literature study with a conceptual and comparative approach, with secondary data sources in the form of statutory regulations, jurisprudence, books and scientific journals which are analyzed using deduction-induction techniques. descriptively. The research results show that legal reasoning cannot be understood as a mechanistic application of formal logical syllogism, but rather as a dialectical process that combines deductive-inductive logic, hermeneutical interpretation, and judge's discretion in legal discovery in order to realizesubstantive justice that goes beyond procedural justice. The research also found an inherent tension between the certainty of legal texts and society's demands for justice, as well as new challenges in the form of the integration of artificial intelligence which has the potential to increase efficiency but carries the risk of reducing the moral dimension of legal reasoning. Applicatively, this research offers an integrative legal reasoning paradigm based on Pancasila values which harmonizes positivism, utilitarianism and natural law, and places technology as an argumentative tool under the control of human ethics. The value of novelty lies in the synthesis between legal hermeneutics and digital literacy to strengthen the quality of reasoning of law enforcement officials so that decisions are more accountable, humane and responsive to the complexity of future law.